Предмет: Алгебра, автор: stvjkk

3x(x^2-4x+3)=
-2b(b^2+2b-3)=
3c^2(-2c^4+c^2+3)=
(-3n^2+2n)•2n=
(2a^2-2a-5)•(-3a)=
помогите пжжжж

Ответы

Автор ответа: olegandrejcenko846
1

Ответ:

3x(x {}^{2}  - 4x + 3) =  \\  = 3x {}^{3 }  - 12x {}^{2}  + 9x

 - 2b(b {}^{2}  + 2b - 3) =  \\  =  - 2b {}^{3}  - 4b {}^{2}  + 6b

3c {}^{2} ( - 2c {}^{4}  + c {}^{2}  + 3) =  \\  =  - 6c {}^{6}  + 3c {}^{4}  + 9c {}^{2}

( - 3n {}^{2}  + 2n) \times 2n =  \\  =  - 6n {}^{3}  + 4n {}^{2}

(2a {}^{2}  - 2a - 5) \times ( - 3a) =  \\  =  - 6a {}^{3}  + 6a {}^{2}  + 15a

Похожие вопросы